Cocopeat-amended leaf mould compost yields quality potted dahlia specimens under shade net intercepting one-third sunlight - Simrat Singh; Aradhna (Advances in Horticultural Science)
Growers in tropical and subtropical climates with higher afternoon solar intensities face challenges while cultivating potted dahlias. Dahlias that are cultivated in pots with limited capacity lose a great deal of their quality when it gets hot outside. Heat waves that occur suddenly damage dahlia plants’ appearance by exposing dry petal margins and marginal leaf blistering. Despite these difficulties, no research has been done to yet to advise growers on the best organic growth medium for dahlias that can maintain high-quality flower production in an appropriate shadow regime. The dahlia cv. Babylon lila rooted cuttings were transplanted into five-gallon (18.92-liter) earthen pots that were filled with six distinct organic growing media formulations. According to our research, dahlia plants grown in a medium containing soil, leaf mould, and cocopeat (50:25:25 v/v) not only produced healthy tubers but also showed better vegetative growth and flowering characteristics. In order to produce higher-quality potted dahlia specimens in hot weather, the study especially advises growing dahlia under shade nets that intercept at least one-third of the incoming solar radiation in areas receiving scorching afternoon sun rays.